Recurrent and Non-Recurrent Mutations of SCN8A in Epileptic Encephalopathy - Wagnon, Jacy L.; Meisler, Miriam H. (Frontiers in Neurology, 2015)
Mutations of the voltage-gated sodium channel SCN8A have been identified in approximately 1% of nearly 1,000 children with early-infantile epileptic encephalopathies (EIEE) who have been tested by DNA sequencing. EIEE caused by mutation of SCN8A is designated EIEE13 (OMIM #614558). Affected children have seizure onset before 18 months of age as well as developmental and cognitive disabilities, movement disorders, and a high incidence of sudden death (SUDEP). EIEE13 is caused by de novo missense mutations of evolutionarily conserved residues in the Nav1.6 channel protein. One-third of the mutations are recurrent, and many occur at CpG dinucleotides. In this review we discuss the effect of pathogenic mutations on the structure of the channel protein, the rate of recurrent mutation, and changes in channel function underlying this devastating disorder.